Factors Affecting COVID-19 Preventive Behaviors of Young Adults based on eHealth Literacy and the Health Belief Model: A Cross-Sectional Study - Hye Seung Choi PhD, RN; Jong-Eun Lee PhD, RN (SAGE Publishing, 2023)
Following the COVID-19 pandemic, disease prevention and preventive behaviors have become crucial for public health. In young adults, the internet is a popular source of health information. However, research that explores the factors associated with disease preventive behaviors based on the eHealth literacy (eHL) and the Health Belief Model (HBM) in young adults is lacking. A cross-sectional study design was used. Snowball sampling was used to recruit the participants through social network services. Proportionate stratified sampling was applied according to age, sex, and education level to mitigate sampling bias. The URL link for the online survey was provided via their mobile phones. A total of 324 participants, aged 20 to 39, completed the structured questionnaires (response rate = 98.2%). Frequency and descriptive statistical analyses, independent t -tests, one-way analyses of variance, Pearson's correlation coefficients, and multiple linear regression analyses were performed. Factors associated with COVID-19 preventive behaviors were COVID-19-related eHL (β = .376, P  < .001) and self-efficacy (β = .221, P  < .001), which were positively associated with COVID-19 preventive behaviors. Boosting self-efficacy and the ability to find, evaluate, and apply health information with sufficient evidence from the Internet can improve COVID-19 preventive behaviors. The government and healthcare personnel should consider psychological factors such as self-efficacy when developing COVID-19 disease prevention behavioral guidelines for the Internet.